Media Sosial dan Live Streaming sebagai Sarana Promosi Efektif: Implementasi Program KKN Konversi di Haura Beauty Store - Nabila Rahma Dani; Asrandi (Macoa : Jurnal Pengabdian kepada Masyarakat, 2026)
The KKN Conversion Program at Haura Beauty Store aims to enhance MSME digital marketing capabilities through the use of social media and live streaming as effective promotional tools. The program involved observation, content creation training, live streaming workshops, digital promotion implementation, and evaluation. The results showed a 28% increase in social media followers, a 35% rise in engagement, and a 20% sales growth after applying digital promotion strategies. The partner also improved in content creation, business account management, and conducting live streaming independently. This program demonstrates that social media and live streaming are effective tools for expanding market reach, enhancing consumer engagement, and strengthening msmes competitiveness in the digital era